Using a Typological Approach in Conducting Local Economic Policy (By The Example of the Gatchina District of Leningrad Region) - Valery Igorevich Belov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article proposes use of the typological approach to improving the management of municipalities. Separating own criteria typology of settlements and the steps of creating a typological groups, the author generates typological groups of municipalities Gatchina district of the Leningrad region, which will further promote the development of model-making.